Tinjauan Yuridis terhadap Bentuk Pertanggungjawaban Hukum terhadap Praktik Nominee dalam Perjanjian Kredit Koperasi Syariah - Amelia, Risky; Lumi, Ninva Eleazar; Tarmudi, Tarmudi (Wajah Hukum, 2026)
The phenomenon of name borrowing in financial institutions, particularly Islamic cooperatives, creates significant legal consequences for both members and the cooperative. Name borrowing occurs when a cooperative member lends or allows his/her name to be used by another party to access financing facilities. From the perspective of civil law, this practice establishes a direct legal relationship between the member listed in the financing contract and the cooperative, even though the actual recipient and user of the funds is another person. This phenomenon has become widespread recently and has become the focus of researchers to examine the impact and solutions to the problems that arise as a result of borrowing names.This study aims to analyze: (1) the form of legal liability borne by cooperative members who engage in name borrowing according to the Indonesian Civil Code (KUHPerdata); and (2) the form of legal protection available to cooperatives against the risk of default arising from such practices. The research method employed is normative-empirical, with primary data obtained through interviews at Koperasi Syariah Benteng Mikro Indonesia (Kopsyah BMI), and secondary data consisting of the Civil Code, the Cooperative Law, and relevant legal literature.The findings indicate that Article 1338 of the Civil Code affirms the principle of pacta sunt servanda, whereby members whose names are stated in the financing contract remain fully responsible for repayment obligations, regardless of who actually benefits from the funds. In the event of default, the consequences are regulated under Articles 1243 and 1267 of the Civil Code, which include performance fulfillment, contract termination, and compensation. Furthermore, if name borrowing is proven to involve bad faith, it may also be categorized as a tort under Article 1365 of the Civil Code.In conclusion, the practice of name borrowing poses legal and financial risks for both members and cooperatives. Legal protection for cooperatives may be pursued through non-litigation mechanisms (collection, warning, restructuring) as well as litigation (lawsuits for breach of contract or tort). To prevent similar cases, cooperatives should strengthen member identity verification, impose financing limits, and enhance legal and Sharia education for their members.